Association between root/coronal caries and individual factors in institutionalised elderly using ICDAS severity and activity - Margarita Usuga-Vacca; Dairo Javier Marin-Zuluaga; Jaime Eduardo Castellanos; Stefania Martignon (BMC, 2021)
Abstract Background Caries in the elderly has been associated with dependence, oral-health status and -care practices. This cross-sectional study aimed to investigate the association between root/coronal caries and individual factors among institutionalised elderly people in Bogotá, Colombia, using the International Caries Detection and Assessment System severity and activity criteria (ICDAS). Methods A total of 226 institutionalised elderly were clinically examined for root and coronal caries in 40 institutions. Caries risk was assessed with Cariogram, and demographics, oral health knowledge and practices, oral health-related quality of life and denture-use habits using a questionnaire. Results Participants (mean age: 80.1 ± 9.3 years; 63.7% female) presented a mean number of 10.8 ± 7.3 teeth and 19.4 ± 18.8 exposed root surfaces. Prevalence of Coronal-ICDAS caries experience (C-ICDAS DF) was of 100% and of 54.4% for C-ICDAS D; mean number of C-ICDAS DFS was 16.76 ± 27.36, with 50.9% of subjects having ≥ one active C-ICDAS DS. Prevalence of Root Caries Index was of 49.1% and of R-ICDAS DF of 46%; mean number of R-ICDAS DFS was 2.03 ± 2.78, with 40.3% of subjects having ≥ one active R-ICDAS DS. Most individuals had a systemic condition (94.2%) and required oral-hygiene assistance (58%). Logistic regression analyses showed significant associations (p < 0.05): for coronal active caries when having over six teeth (OR: 2.7), and for root caries, when having coronal caries (OR: 2.41), being a man (OR: 1.95), and having over 14 teeth (OR: 0.30). Those presenting with > eight exposed root surfaces were 4.04 more likely to have root caries and 2.4 times more likely to have active root caries. Conclusion In the institutionalised elderly population in Bogotá significant associations were found, both for the presence as for the activity status of root and coronal caries, with individual clinical factors including coronal caries, exposed root surfaces and number of teeth.